High Food Prices, Latin American and the Caribbean Responses to a New Normal - World Bank (Washington, DC, 2014)
Yet the current situation differs from 2007-2008 in critical respects. First, recent international price increases are more widespread across agricultural commodities than in 2008, when price spikes were led by few grains such as wheat and rice. Second, natural resources are affecting food production: land and water constraints are more binding than in the past and weather induced production shortfalls are more of a factor now than it was 2008. Climate change also adds to this uncertainty, particularly since a larger share of grain exports are being produced in areas more exposed to climate variability. Third, long term structural changes in the markets are more clearly a major factor this time, as demand for feed and income-elastic foods under sustained and widespread income growth in emerging countries is increasing steadily. Fourth, the global stocks/use ratio for major cereals, which used to hover in the range of 30-35 percent in the 1980s and 1990s, has been around 20 percent after 2003 due largely to long-term policy changes in high-income countries; and stocks of some critical players are now at all-time lows. Global markets are currently experiencing the second sharp spike in food prices in the last four years. While no one has a crystal ball to predict with confidence the future prices of food products, there are good reasons to believe that structural factors affecting both supply and demand, discussed in this report, have recently evolved in ways that will increase the average levels and volatility of prices above those of recent decades. Ensuring that the world's populations, and particularly vulnerable groups, are adequately fed is one of the most important contributions of the World Bank to the global public good's agenda. This report describes how the current situation is affecting countries in the Latin America and Caribbean region, including the impact on different groups within countries, and proposes strategies to best assist our client countries in responding.